(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
In article on the basis of the analysis of the novel O. Kobylyanska «The Apostle mobile» Procman branching, the complexity and interaction of the system of images of works, which makes it possible to identify the author’s particular approach to the creation of artistic images.